A general LC-MS-based RNA sequencing method for direct analysis of multiple-base modifications in RNA mixtures. Issue 20 (3rd September 2019) - Zhang, Ning; Shi, Shundi; Jia, Tony Z; Ziegler, Ashley; Yoo, Barney; Yuan, Xiaohong; Li, Wenjia; Zhang, Shenglong
Abstract: A complete understanding of the structural and functional potential of RNA requires understanding of chemical modifications and non-canonical bases; this in turn requires advances in current sequencing methods to be able to sequence not only canonical ribonucleotides, but at the same time directly sequence these non-standard moieties. Here, we present the first direct and modification type-independent RNA sequencing method via introduction of a 2-dimensional hydrophobic end-labeling strategy into traditional mass spectrometry-based sequencing (2D HELS MS Seq) to allow de novo sequencing of RNA mixtures and enhance sample usage efficiency. Our method can directly read out the complete sequence, while identifying, locating, and quantifying base modifications accurately in both single and mixed RNA samples containing multiple different modifications at single-base resolution. Our method can also quantify stoichiometry/percentage of modified RNA versus its canonical counterpart RNA, simulating a real biological sample where modifications exist but may not be 100% at a particular site in the RNA. This method is a critical step towards fully sequencing real complex cellular RNA samples of any type and containing any modification type and can also be used in the quality control of modified therapeutic RNAs.